Penerapan Media Sosial Instagram Sebagai Sumber Materi Dikalangan Mahasiswa - Ermitati Sinaga; Firda Artauli Melina Sianturi; Nazmi Hayani Situmorang; Ribka Riama Hutajulu; Rincawani Sidabalok; Suryani Layla Sitompul; Jamaludin J (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Social media is software that has been widely used by humans in this era of globalization, where social media is used as communication material in various corners of the world. Social media is very diverse, where currently young people are more closely connected to the Instagram application. The aim of this research is to evaluate the effectiveness of using Instagram as a development medium in the field of design, focusing on Fashion Design students. Where Instagram social media can provide source material for Fashion Design students in designing. The research method used in this research uses a qualitative approach obtained from a literature review regarding the application of media for learning media, material sources, and the use of Instagram among students. Where students can access material sources from social media Instagram.